A Film Aesthetic to Discover - Andrew, Dudley (Cinémas, 2007)
AbstractChallenging today’s ascendant digital aesthetic, this essay retraces one powerful line of French theory which treats film as an art which “discovers” significance rather than “constructs” meaning. Champions of today’s technology find that the digital at last permits complete control over image construction and therefore over “cinema effects.” Opposed to this aesthetic which targets the audience, the French aesthetic stemming from Roger Leenhardt and André Bazin concerns itself with the world the filmmaker engages. An interplay of presence and absence, as well as of human agency in the non-human environment, characterizes the French aesthetic at each phase of the filmic process: recording, composing and projecting. This article focuses on the central phase, composing, and on the terminological shift from “image” to “shot” picked up after Bazin by the Nouvelle Vague and passed forward to our own day through Serge Daney. In short, there is a Cahiers du cinéma line of thought, applied to questions of editing, which emphasizes the filtering implied in shots and the ellipses implied in their order. Conventional editors, on the other hand, manipulate or juxtapose images (using processes known as “compositing” today). The Cahiers line of thought developed in symbiosis with neo-realism and with a spate of post-war essay films of the “caméra-stylo” sort (Resnais, Franju) wherein editing works to cut away and filter out the inessential so that a mysterious or abstract subject can be felt as beginning to appear. Rivette, Rohmer and Godard have passed this line of thought on to a later generation represented by Philippe Garrel and a still later one for which Arnaud Desplechin stands as a good example.